Strategi Perencanaan Program Marketing PR PT Good Farmers “Ada Susu Untuk Mereka” - Dewi Retno Budiastuti; Ita Suryani; Regina Febriyanti (Jurnal Public Relations (J-PR), 2021)
The PR Marketing Program "Ada Susu Untuk Mereka" is an activity organized by PT Good Farmers in reaching out to help improve the nutrition of Indonesian children by providing free ready-to-drink milk for underprivileged children in slum areas in the DKI Jakarta area. In addition to providing milk, the “Ada Susu Untuk Mereka” activity also provides illustrated fairy tale books and education about the importance of drinking milk, its growth and nutritional benefits. During the growth period, children must be given a balanced diet. Giving milk aims to maintain the child's immune system and help the process of growth and development. The PR Marketing Program “Aku Ada Untuk Mereka” is PT Good Farmer's strategy in increasing brand awareness, brand image and product brand engagement. The purpose of this study was to find out how the PR Marketing program planning strategy of PT Good Farmer in increasing brand awareness, brand image and product brand engagement. Using a case study research method that requires data from various sources and various instruments in data collection. The results showed that the brand awareness, brand image and brand engagement strategies carried out by PT Good Formaer became a form of two-way communication and interaction between a brand and its consumers. With the establishment of brand awareness, brand image and brand engagement, there will also be high loyalty from customers.